The awareness and attitude towards Islamic banking: a study in Malaysia - Saiti, Buerhan (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga Yogyakarta, 2015)
The purpose of this study is to establish the level of awareness that Malaysians have in relation to the culture of Islamic banking, the attitude of Malaysians towards Islamic banking and a ranking of the bank selection criteria of Malaysians – and for each part of the study, to see if Muslim responses are different from non-Muslim responses. A sample of 150 Muslim and non-Muslim customers in Klang Valley was surveyed utilizing a questionnaire containing specific questions relating to the awareness and attitudes of Islamic banking to their ranking of the services required. It is found that the Muslims are more aware toward the culture of Islamic banking, and as consequences, be more aware of the meaning of fundamental terms used in Islamic banking and finance.In the case of the attitudes towards Islamic banks, there were many differences in attitudes between Muslims and non-Muslims in country with majority of Muslims. In the context of bank selection criteria, there are four significant differences among Muslims and non-Muslims such as, mass media advertising, credit on favorable terms, financial counseling and location near my place of work, while the others 18 criteria shows no significant difference. The findings can be utilize by banks to measure the level of attitudes and acceptance towards Islamic Banking among Muslims and non-Muslim and for those who is considering setting up an Islamic banking operations in the country with majority of Muslims.